INTEGRATED APPROACH FOR DIABETES THROUGH LIFE STYLE MODIFICATIONS AND YOGA: A CRITICAL REVIEW (AYUSHDHARA, 2021)
Diabetes mellitus is defined as multiple etiological disorder characterized by chronic hyperglycemia and disturbed of metabolism leads into defective insulin secretion, action or both. Research showed 150 million people have diabetes mellitus worldwide, which can be doubled by the year 2025. This tremendous sudden increase is due to population growth, ageing, unhealthy diets, obesity and sedentary lifestyles. In contemporary science diabetes management includes uses of oral hypoglycemic agents and insulin injections still blood sugar level remains uncontrolled and may leads to further complications. In Ayurveda characteristic features of diabetes has been described under Madhumeha in which treatment principles have been explained beautifully in detail which includes Shodhana therapy, Shamana therapy, diet and Yogic exercise. Through various studies we come across that there have been lots of research works done on role of Ayurveda and yoga in diabetes mellitus. In this article an attempt has been made to collect various data published by CCRAS, Ministry of AYUSH, ICMR and CSIR has. Along with data available on PubMed, Medline, Google Scholar, AYUSH research portal and various online journals based on some clinical studies. So, that a multidimensional approach can be made through these resources and apply to cure the patient and improve quality of life.